Autologous bone marrow‐derived mesenchymal stromal cell therapy with early tacrolimus withdrawal: The randomized prospective, single‐center, open‐label TRITON study. Issue 9 (18th March 2021) - Reinders, Marlies E. J.; Groeneweg, Koen E.; Hendriks, Sanne H.; Bank, Jonna R.; Dreyer, Geertje J.; de Vries, Aiko P. J.; van Pel, Melissa; Roelofs, Helene; Huurman, Volkert A. L.; Meij, Paula; Moes, Dirk J. A. R.; Fibbe, Willem E.; et al.
Abstract : After renal transplantation, there is a need for immunosuppressive regimens which effectively prevent allograft rejection, while preserving renal function and minimizing side effects. From this perspective, mesenchymal stromal cell (MSC) therapy is of interest. In this randomized prospective, single‐center, open‐label trial, we compared MSCs infused 6 and 7 weeks after renal transplantation and early tacrolimus withdrawal with a control tacrolimus group. Primary end point was quantitative evaluation of interstitial fibrosis in protocol biopsies at 4 and 24 weeks posttransplant. Secondary end points included acute rejection, graft loss, death, renal function, adverse events, and immunological responses. Seventy patients were randomly assigned of which 57 patients were included in the final analysis (29 MSC; 28 controls). Quantitative progression of fibrosis failed to show benefit in the MSC group and GFR remained stable in both groups. One acute rejection was documented (MSC group), while subclinical rejection in week 24 protocol biopsies occurred in seven patients (four MSC; three controls). In the MSC group, regulatory T cell numbers were significantly higher compared to controls ( p = .014, week 24). In conclusion, early tacrolimus withdrawal with MSC therapy was safe and feasible without increased rejection and with preserved renal function. MSC therapy is a potentially useful approach after renal transplantation. Abstract : TRITON, a randomized, prospective, single‐center, open‐label study, shows that autologous mesenchymal stromal cell therapy and early tacrolimus withdrawal was feasible and safe, without increased rejection and with preserved renal function.